Characterization of Immunostimulatory CpG-Rich Sequences from Different Bifidobacterium Species - Ménard, Odile (American Society for Microbiology (ASM), 2010)
The beneficial effects of Bifidobacterium are partly due to its immunostimulatory properties. These immunostimulatory properties may be linked to the presence of unmethylated CpG motifs specific to bacterial DNA, which may induce a TH1 response by activating Toll-like receptors (TLR). Using in silico analyses, PCR amplification, and dot blotting, we characterized the CpG content of various bifidobacterial strains and evaluated the immunostimulatory properties and genomic heterogeneity of these motifs in the genus. Our in silico study, based on entire genome sequences from five bifidobacterial strains, showed that Bifidobacterium genomes contain numerous CpG motifs, including 5′-purine-purine-CG-pyrimidine-pyrimidine-3′ and 5′-purine-TCG-pyrimidine-pyrimidine-3′ motifs, and biologically active sequences previously identified in lactic acid bacteria. We identified four CpG-rich sequences with Bifidobacterium longum NCC2705. Two sequences with a percent G+C of about 68% included 14 and 16 CpG motifs. Two sequences with a percent G+C of about 60% included 16 and 6 CpG motifs. These sequences induce the production of monocyte chemoattractant protein 1 (MCP-1) and tumor necrosis factor alpha (TNF-α) through a pattern of TLR9 stimulation on RAW 264.7 macrophages. No link could be established between their immunostimulatory properties, the number of CpG motifs, and percent G+C. We investigated inter- and intraspecies heterogeneity in 71 strains of various origins. These sequences were highly conserved in the genus. No link was found between the presence of the CpG-rich sequence and the origin of the strains (healthy, allergic, or preterm infants). The high frequency of CpG motifs in the DNA of Bifidobacterium may play an important role in the immunostimulatory properties of commensal or probiotic bifidobacterial strains.